Music and Urban Youth Identities. A Study of Ghetto Youth Identities in Contemporary Culture and Politics in Zimbabwe - Vögele, Pius Jonas (International Library of African Music, 2025)
pages: 81-82
Keywords: Book reviews; Music; Culture; Cultural Identity; Youth Culture; Urban Youth Identity; Identity; Ghetto; Zimbabwe; African Music; Politics